TECHNICAL ANALYSIS OF BOLLINGER BANDS INDICATORS AND RELATIVE STRENGTH INDEX IN DETERMINING SELL AND BUY SIGNALS OF BITCOIN CRYPTOCURRENCY COMMUDITIES - I Made Krisna Wardana; I Gde Kajeng Baskara (Adisam Publisher, 2024)
This research aims to analyze the accuracy of the Bollinger Bands and Relative Strength Index (RSI) technical indicators in determining buy and sell signals on Cryptocurrency, especially Bitcoin. Based on data from 2021 to 2023, there has been a significant increase in the number of Cryptocurrency investors in Indonesia. Bollinger Bands measure volatility and help determine the right time to enter or exit the market, while RSI helps identify overbought or oversold conditions. The research results show that of the total of 15 signals identified using the daily timeframe, Bollinger Bands succeeded in providing accurate predictions 10 times with an accuracy rate of 66.7%. The RSI indicator shows an accuracy rate of 60%, with 3 out of 5 signals successful. Bollinger Bands tend to provide more signals because they base their predictions on price movements against their own band lines, RSI focuses more on overbought and oversold conditions, providing sharper and more accurate signals, but the limitations of both indicators are seen in bullish market conditions, where they do not there is a buy signal that is generated when the price of Bitcoin experiences a significant increase. This research concludes that although both indicators have their respective advantages and disadvantages, traders can use them accurately to identify trading opportunities on Bitcoin.